The Metamorphosis of the Paraguayan Right - Soler, Lorena Marina (2023)
The Metamorphosis of the Paraguayan Right After more than half a century of nearly uninterrupted Colorado Party rule, gains by an extremist candidate from the fringes show signs that traditional parties’ power could be eroding.